A clinical study of Fournier’s gangrene and use of honey dressing in treatment - Ugane, Subodh P.; Kalbagwar, Shrikant K.; Kurane, Sanjot B. (International Journal of Research in Medical Sciences, 2018)
Abstract- background Fournier’s gangrene is necrotizing fasciitis involving genitals and perineal regions. Fournier’s gangrene is a surgical emergency. If not treated immediately it spreads rapidly causing septicemia leading to death. Mainstay of treatment is surgical and regular dressing. Various dressing materials are available like eusol, in our study we use Honey as dressing material. This is a small work to attempt to study incidence, etiology and pathogenesis and use of dressing for the treatment of Fournier’s Gangrene. Materials and methods in our study we study 40 male patients of Fournier’s gangrene. We studied clinico- pathology of disease and use of honey dressing for the management of Fournier’s gangrene. Out of 40 patients 18 were treated with honey as dressing material and remaining 22 with eusol. Results- 40 patients were admitted and majority of patients were in age group > 60 years mean age was 54.08 _ 15.47 years. Majority of patients belonged to lower socioeconomic class 82.5%. Most of patients presented in hospital within 7 days of initial symptoms. In this study etiological causes found in 85% of patients and among which most common were urogenital causes 32.5%. Majority of patients had chronic alcoholism and bad hygiene as predisposing factors. 25% were associated with diabetes mellitus. In this study 12% of patients were HIV positive. Most common organism found in pus culture was E.coli (42.5%) followed by Coagulase negative Staphylococci in 32.5%, Klebsiella in 12.5%, Pseudomonas in 7.5% and no organism were isolated in 5%.Mean days required for healthy granulation by honey dressing was 9.62+- 4.5 days and for eusol was 10.5 +- 3.79 days. In our study mortality was 22.5%.